2006
DOI: 10.1161/01.str.0000204239.49586.55
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Direct Thrombus Imaging in Moderate Carotid Artery Stenosis

Abstract: Stroke welcomes Letters to the Editor and will publish them, if suitable, as space permits. They should not exceed 750 words (including references) and may be subject to editing or abridgment. Please submit letters in duplicate, typed double-spaced. Include a fax number for the corresponding author and a completed copyright transfer agreement form (published in every issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Our study also reported no discernable hemorrhage post-sectioning. Fortunately, the intra-plaque contrast properties of calcium and hemorrhage have previously been established [26,27]. Ultra short echo time sequences have separately been applied to quantify calcium [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also reported no discernable hemorrhage post-sectioning. Fortunately, the intra-plaque contrast properties of calcium and hemorrhage have previously been established [26,27]. Ultra short echo time sequences have separately been applied to quantify calcium [28].…”
Section: Discussionmentioning
confidence: 99%
“…A better-designed future study may include a larger sample size, homogenous inclusion criteria and imaging protocol, multiple races, and fair gender distribution. Additionally, the new developed imaging techniques for detecting IPH 29 and thrombus 30 might be helpful in characterizing vulnerable plaques in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Takaya et al showed that among patients who initially had an asymptomatic 50–79% carotid stenosis, arteries with thinned or ruptured fibrous caps, intraplaque haemorrhage or large lipid rich/necrotic cores, by MRI, were associated with the occurrence of subsequent cerebrovascular events 23. Similarly, Daniels et al showed the potential value of MRI and detection of intraplaque haemorrhage in decision making for moderate carotid stenosis 24. Our study supports these findings and adds weight to the argument that plaque characterisation with MRI is a potentially valuable clinical tool for risk stratification.…”
Section: Discussionmentioning
confidence: 99%